States of disorder understanding state failure and intervention in the periphery - Halvorson, Daniel (Ashgate Pub., 2013)
This book is a comparative history of the conditions under which great powers and their close allies care enough about disorder from the periphery to mount costly armed interventions to reverse what they deem to be state 'failure'.